Development Of Novel Liposome-Encapsulated Combretastatin A4 Acylated Derivatives: Prodrug Approach For Improving Antitumor Efficacy - Gu Y (Dove Medical Press, 2019)
Yongwei Gu,1,2,* Juanjuan Ma,2,* Zhiqin Fu,1,2,* Youfa Xu,1,2 Baoan Gao,1,2 Jianzhong Yao,3 Wei Xu,1 Kedan Chu,1 Jianming Chen1,2 1Department of Pharmacy, Fujian University of Traditional Chinese Medicine, Fujian 350108, People’s Republic of China; 2Shanghai Wei Er Biopharmaceutical Technology Co., Ltd., Shanghai 201707, People’s Republic of China; 3School of Pharmacy, Second Military Medical University, Shanghai 200433, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wei Xu; Jianming ChenDepartment of Pharmacy, Fujian University of Traditional Chinese Medicine, Fujian 350108, People’s Republic of ChinaTel/fax +86-591-22861693; +86-21-31198900-8949Email 2000017@fjtcm.edu.cn; chenjm0711@163.comPurpose: The objective of the present study was to develop a liposomal drug delivery system based on combretastatin A4 (CA4) prodrugs modified with varying alkyl chains and investigate the in vitro drug conversion from prodrug and in vivo antitumor effect.Methods: The prodrug of CA4 was synthesized with stearyl chloride (18-carbon chain), palmitoyl chloride (16-carbon chain), myristoyl chloride (14-carbon chain), decanoyl chloride (10-carbon chain), and hexanoyl chloride (6-carbon chain) at the 3′-position of the CA4. Subsequently, it was encapsulated with liposomes through the thin-film evaporation method. Furthermore, the characteristics of prodrug-liposome were evaluated using in vitro drug release, conversion, and cytotoxicity assays, as well as in vivo pharmacokinetic, antitumor, and biodistribution studies.Results: The liposome system with loaded CA4 derivatives was successfully developed with nano-size and electronegative particles. The rate of in vitro drug release and conversion was reduced as the fatty acid carbon chain lengthened. On the contrary, in vivo antitumor effects were improved with the enlargement of the fatty acid carbon chain. The results of the in vivo pharmacokinetic and tissue distribution studies indicated that the reduced rate of CA4 release with a long carbon chain could prolong the circulation time and increase the drug concentration in the tumor tissue.Conclusion: These results suggested that the release or hydrolysis of the parent drug from the prodrug was closely related with the in vitro and in vivo properties. The slow drug release of CA4 modified with longer acyl chain could prolong the circulation time and increase the concentration of the drug in the tumor tissue. These effects play a critical role in increasing the antitumor efficacy.Keywords: combretastatin A4, liposome, prodrug, drug release, anticancer